2020
DOI: 10.3389/fnagi.2020.597811
|View full text |Cite
|
Sign up to set email alerts
|

AChRs Degeneration at NMJ in Aging-Associated Sarcopenia–A Systematic Review

Abstract: Sarcopenia is an aging process with a decline of skeletal muscle mass and function, which is a challenging public health problem with reduced quality of life in patients. The endplate, the post-synaptic part of the neuromuscular junction (NMJ), occupies 0.1% of the myofiber surface area only, but is composed of millions of acetylcholine receptors (AChRs) that are efficient in binding to acetylcholine (ACh) and triggering skeletal muscle contraction. This systematic review aims to examine aging-associated alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 69 publications
(354 reference statements)
1
22
0
1
Order By: Relevance
“…It has been reported by Klitgaard et al that co-expression of different isoforms of MHC in a single muscle fiber increases with age, suggesting a continuous shift in the type of muscle fiber [ 15 ], and it is demonstrated that muscles in elderly individuals contain more slow muscle fibers that reduce contraction ability [ 16 ]. This also supports endplate fragmentation and functional denervation [ 17 ].…”
Section: Introductionsupporting
confidence: 69%
“…It has been reported by Klitgaard et al that co-expression of different isoforms of MHC in a single muscle fiber increases with age, suggesting a continuous shift in the type of muscle fiber [ 15 ], and it is demonstrated that muscles in elderly individuals contain more slow muscle fibers that reduce contraction ability [ 16 ]. This also supports endplate fragmentation and functional denervation [ 17 ].…”
Section: Introductionsupporting
confidence: 69%
“…Endplate fragmentation is a multi-stage disassociation of the NMJ typically seen during aging. This process is marked by a dispersal of clustered AChRs, AChR type switching, and increased turnover rates of the receptor [ 118 , 119 ]. As a way to compensate for fragmentation, increased enzyme levels of acetylcholinesterase and increased levels of acetylcholine (ACh) release from the synaptic terminal were detected [ 119 ].…”
Section: Peripheral Nerve Involvement In Aging and Atrophymentioning
confidence: 99%
“…Age-related disruptions in the structure and function of the NMJ, which enables communication between the nervous and skeletal muscle systems, have also been described ( Badawi and Nishimune, 2018 ; Dobrowolny et al, 2021 ; Fuertes-Alvarez and Izeta, 2021 ; Pratt et al, 2021 ). Age-related plasticity of the NMJ include fragmentation of the post-synaptic endplate, as well as increased length and branch points of pre-synaptic nerve terminal endings ( Deschenes et al, 2016 , 2018 ; Bao et al, 2020 ), with greater dispersion, and a smaller number of acetylcholine (ACh) containing pre-synaptic vesicles ( Petralia et al, 2014 ; Ivannikov and Van Remmen, 2015 ; Badawi and Nishimune, 2018 ). Numerous reports have also indicated that compared to young ones, aged neuromuscular systems are more vulnerable to the detrimental effects of disuse ( Robbins, 1992 ; Pandya and Patani, 2021 ), suggesting that at times of enhanced natural neuromuscular plasticity, imposed neuromuscular disuse elicits more pronounced morphological and physiological remodeling than during the mature, adult phase of life that comprises much of the lifespan ( Fahim, 1989 ; Deschenes and Wilson, 2003 ; Wilson and Deschenes, 2005 ).…”
Section: Discussionmentioning
confidence: 99%